2021
DOI: 10.3390/ijms22041954
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and Engineered Large Animal Models of Neurofibromatosis Type 1

Abstract: Animal models are crucial to understanding human disease biology and developing new therapies. By far the most common animal used to investigate prevailing questions about human disease is the mouse. Mouse models are powerful tools for research as their small size, limited lifespan, and defined genetic background allow researchers to easily manipulate their genome and maintain large numbers of animals in general laboratory spaces. However, it is precisely these attributes that make them so different from human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 118 publications
(207 reference statements)
1
13
0
Order By: Relevance
“…Importantly, the efficacy of chemotherapy in human PNST is profoundly affected by the patient's neurofibromatosis type 1 (NF1) tumor predisposition syndrome status (25). It has been suggested that dogs with PNST may represent a naturally occurring model of NF1, though genetic studies to confirm this are lacking (33). This presents an intriguing topic for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the efficacy of chemotherapy in human PNST is profoundly affected by the patient's neurofibromatosis type 1 (NF1) tumor predisposition syndrome status (25). It has been suggested that dogs with PNST may represent a naturally occurring model of NF1, though genetic studies to confirm this are lacking (33). This presents an intriguing topic for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, tumor cells undergo spontaneous loss of heterozygosity mimicking the second-hit phenomenon that occurs in humans[ 21 ]. Holstein cattle have also been used as preclinical model for human NF[ 22 ]. Large, comparative genomic studies in human, canine, and rodent models of NF1 would be of value to help identify commonly affected and targetable pathways that may serve as drug targets or potential biomarkers for NF1 patients[ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specific achievements included identifying a drug that moved into clinical trials for NF2, the generation of two first-ever minipig models for NF, performing a first-ever full omics analysis of a set of schwannomatosis tumor samples for study, and generating game-changing findings for low-grade glioma. The Synodos achievements have led to new investigational studies as well as 19 (at time of writing) publications in high-visibility medical journals [12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Synodos Projects Demonstrated a Range Of Successes That Were...mentioning
confidence: 99%